2016
DOI: 10.1016/j.bjorl.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

The role of aspirin desensitization in patients with aspirin-exacerbated respiratory disease (AERD)

Abstract: Aspirin desensitization, when tolerated, was effective in patients with AERD and with poor clinical/surgical response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 25 publications
3
17
1
2
Order By: Relevance
“…A similar review of literature data made by Adelman et al [24] highlights the clear improvement in sinonasal symptom severity and frequency, endoscopy score, quality of life, and asthma severity. In postoperative treatment, aspirin desensitization or inclusion of LTRAs are suggested [25, 26]. In the literature cited, in contrast to our observations, an improvement in the sense of smell was found more often together with improved SNOT-22 values.…”
Section: Discussioncontrasting
confidence: 55%
“…A similar review of literature data made by Adelman et al [24] highlights the clear improvement in sinonasal symptom severity and frequency, endoscopy score, quality of life, and asthma severity. In postoperative treatment, aspirin desensitization or inclusion of LTRAs are suggested [25, 26]. In the literature cited, in contrast to our observations, an improvement in the sense of smell was found more often together with improved SNOT-22 values.…”
Section: Discussioncontrasting
confidence: 55%
“…In total, 3330 references were imported for screening, and 24 studies were included for extraction (Fig. and Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, not all studies reported in depth the details of their NSSs. In total, NSSs were reported in 14 studies and 13 studies (92.9%) showed improvement with desensitization.…”
Section: Resultsmentioning
confidence: 99%
“…This review identified 1 systematic review and 7 RCTs evaluating the impact of aspirin desensitization on symptoms of CRSwNP in AERD (Table ). Three cohort studies and 12 case series were excluded from analysis due to a low level of evidence. The highest‐quality study by Xu et al .…”
Section: Results: Contemporary Management Of Crs In Aerdmentioning
confidence: 99%